IMPLEMENTASI KEBIJAKAN PENDIDIKAN DALAM PROGRAM BANTUAN OPERASIONAL SEKOLAH - Fika Ayu Lestari; Muh Rahim; Lilis Suriani (Institusi Agama Islam Negeri (IAIN) Bone, 2019)
Regional autonomy authorizes local governments to be responsible for each region. Governmentpolicies that are expected to improve the education that the School Operational Assistance policy.BOS management is the responsibility of each school run by the Head of School, School Treasurer,and the School Committee. This research is a descriptive qualitative study aimed to determine theBOS policy implementation. The problem that occurs is the lack of BOS funds received by someschools, the school is less timely in reporting use of the funds, the lack of ability of teachers whobecame treasurer or BOS fund managers, as well as the lack of clear information received relatedpublic free schools. Therefore, the necessary training or upgrading capabilities for the officersinvolved on the BOS, transparency through the media available, more details of the informationprovided to the public through the medium of television, radio, or print media related to the notionof free schooling and explained with thorough and sustainable.